Pengaruh Kebiasaan Diri Yang Buruk dan Kebiasaan di Era New Normal Terhadap Kinerja Driver Gojek di Salatiga - Haumahu, Novy; Franksiska, Rosaly (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
Gojek is an application commonly used in Indonesia, based on a survey by the Yayasan Lembaga Konsumen Indonesia (YLKI). Since the Covid-19 pandemic emerged, various adaptations to new habits called the New Normal have been implemented, causing a change in the lifestyle of Gojek drivers. Another habit studied was bad habit, which according to the American Psychological Association is common in millennials and causes them to experience stress. The purpose of this study was to analyse whether bad habits and the New Normal habit affect Gojek drivers’ performance in Salatiga. The respondents in this study were 160 Gojek drivers. Respondents' answers regarding bad habits are high, especially on the habit of drivers who sit for too long, in their routine of riding motorcycles. Based on the answers, the habits of the new normal era were also high, especially in the understanding of drivers in using masks correctly. This research was conducted using a quantitative causality method. The hypothesis testing using multiple linear regression analysis shows that bad habits and new normal habits simultaneously affect drivers’ performance. On other hand, the habits of the new normal habit positively affect drivers’ performance, while bad habits have no effect on the performance of Gojek drivers in Salatiga even though it was high.